2021
DOI: 10.1111/avsc.12585
|View full text |Cite
|
Sign up to set email alerts
|

Grassland management and land use history shape species composition and diversity in Transylvanian semi‐natural grasslands

Abstract: Aims Semi‐natural grasslands are among the most biodiverse habitats in Europe, and they are of great conservation and agricultural value. However, changes in land use like grazing intensification and the cessation of traditional management have dramatic effects on the extent and biodiversity of these ecosystems. In this study we investigated how current management practices and land use history shape species composition and diversity patterns in semi‐natural grasslands of the Eastern hills of the Cluj region. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Each phytocenosis, with its own characteristics, can be influenced by humans and, therefore, new types of grasslands appear [ 2 ]. Organized experiments, both nationally and internationally, have shown that the intensification of grassland systems greatly reduces the specific richness, installing valuable forage species (generally nitrophilic species), which offer rich biomass crops and high-quality fodder [ 13 , 17 , 24 , 25 , 26 ]. The formation of specific groups as a result of the application of inputs demonstrates that fertilizer treatments have produced major changes in the phytocenosis of grasslands [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each phytocenosis, with its own characteristics, can be influenced by humans and, therefore, new types of grasslands appear [ 2 ]. Organized experiments, both nationally and internationally, have shown that the intensification of grassland systems greatly reduces the specific richness, installing valuable forage species (generally nitrophilic species), which offer rich biomass crops and high-quality fodder [ 13 , 17 , 24 , 25 , 26 ]. The formation of specific groups as a result of the application of inputs demonstrates that fertilizer treatments have produced major changes in the phytocenosis of grasslands [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, long time uncultivated linear-shaped habitats in verges covered by dry grassland fragments in the Great Hungarian Plain maintained an average diversity of 2.2 [ 37 ]. In Transylvania (Romania), for grazed grasslands and hand mowed grasslands, Shannon diversity values were around 2.7–3.2 [ 38 ], whereas, for mountainous semi-natural grasslands, diversity values of 2.36–2.68 were reported, depending on various conservation treatments [ 39 ]. Beyond local geographical regions, like in Sweden, grazed semi-dry grasslands’ diversity ranged from 2.4 to 3.3 [ 40 ], whereas grasslands developed on limestone bedrock maintained diversity of 2.2–3.1 [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies indicate that the species composition of communities, their diversity and the occurrence of rare species are related not only to the current management but also to the habitat history [21,22]. The historical land use and land use sequences shaped the vegetation of Swedish semi-natural grassland more so than the current management.…”
Section: Introductionmentioning
confidence: 99%
“…The highest diversities of grassland plants have been found in pastures continuously grazed since the 18th century [21]. The continuity of extensive mowing and grazing has a positive effect on the occurrence of grassland and forest edge specialist species [22]. The spatial context is also important: the present and historical habitat connectivity influences fine-scale plant species diversity in grazed temperate semi-natural grasslands [23].…”
Section: Introductionmentioning
confidence: 99%